Anaerobic peroxisomes in Entamoeba histolytica metabolize myo-inositol. - Zdeněk Verner; Vojtěch Žárský; Tien Le; Ravi Kumar Narayanasamy; Petr Rada; Daniel Rozbeský; Abhijith Makki; Darja Belišová; Ivan Hrdý; Marie Vancová; Corinna Lender; Constantin König; et al. (PLoS Pathogens, 2021)
Entamoeba histolytica is believed to be devoid of peroxisomes, like most anaerobic protists. In this work, we provided the first evidence that peroxisomes are present in E. histolytica, although only seven proteins responsible for peroxisome biogenesis (peroxins) were identified (Pex1, Pex6, Pex5, Pex11, Pex14, Pex16, and Pex19). Targeting matrix proteins to peroxisomes is reduced to the PTS1-dependent pathway mediated via the soluble Pex5 receptor, while the PTS2 receptor Pex7 is absent. Immunofluorescence microscopy showed that peroxisomal markers (Pex5, Pex14, Pex16, Pex19) are present in vesicles distinct from mitosomes, the endoplasmic reticulum, and the endosome/phagosome system, except Pex11, which has dual localization in peroxisomes and mitosomes. Immunoelectron microscopy revealed that Pex14 localized to vesicles of approximately 90-100 nm in diameter. Proteomic analyses of affinity-purified peroxisomes and in silico PTS1 predictions provided datasets of 655 and 56 peroxisomal candidates, respectively; however, only six proteins were shared by both datasets, including myo-inositol dehydrogenase (myo-IDH). Peroxisomal NAD-dependent myo-IDH appeared to be a dimeric enzyme with high affinity to myo-inositol (Km 0.044 mM) and can utilize also scyllo-inositol, D-glucose and D-xylose as substrates. Phylogenetic analyses revealed that orthologs of myo-IDH with PTS1 are present in E. dispar, E. nutalli and E. moshkovskii but not in E. invadens, and form a monophyletic clade of mostly peroxisomal orthologs with free-living Mastigamoeba balamuthi and Pelomyxa schiedti. The presence of peroxisomes in E. histolytica and other archamoebae breaks the paradigm of peroxisome absence in anaerobes and provides a new potential target for the development of antiparasitic drugs.